2020
DOI: 10.1186/s13071-020-04337-2
|View full text |Cite
|
Sign up to set email alerts
|

High levels of third-stage larvae (L3) overwinter survival for multiple cattle gastrointestinal nematode species on western Canadian pastures as revealed by ITS2 rDNA metabarcoding

Abstract: Background The ability of infective larvae of cattle gastrointestinal nematode (GIN) species to overwinter on pastures in northerly climatic zones with very cold dry winters is poorly understood. This is an important knowledge gap with critical implications for parasite risk assessment and control. Methods Infective third-stage larvae (L3) were quantified in samples of fecal pats, together with adjacent grass and soil, before and after winter on three farms in southern, central and northern Alberta. Nemabiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Humid conditions support infective larvae to survive. 27 There were 21 cases of colic horse with dental disease in our sample (Table 2). Special treatment is needed due to the condition of the horses' teeth, which are not suitable for chewing hard grass.…”
Section: Discussionmentioning
confidence: 93%
“…Humid conditions support infective larvae to survive. 27 There were 21 cases of colic horse with dental disease in our sample (Table 2). Special treatment is needed due to the condition of the horses' teeth, which are not suitable for chewing hard grass.…”
Section: Discussionmentioning
confidence: 93%
“…The recovery rates of the grass and fecal L3 protocols were 22.0% and 14.4%, respectively, and were applied to the calculation of available L3. Grass samples were processed following a flotation and sieving protocol, as described by Wang et al [ 13 ]. The total number of L3 that migrated from one fecal pat onto grass ( L3 g) was calculated as follows: where L3 s is the number of L3 in each sampling unit.…”
Section: Methodsmentioning
confidence: 99%
“…These locations differ from more temperate regions in several important ways, including the occurrence of extremely cold and dry winters and drier summers with sporadic but sometimes heavy precipitation [ 16 ]. Recent work has shown that L3 of both Ostertagia ostertagi and Cooperia oncophora can survive over the winter in significant numbers on pastures in western Canada, despite the very low temperatures and low humidity at this time of the year, with the fecal pat being an important refuge [ 13 ]. Fecal egg counts are known to increase over the summer grazing season in beef cattle in western Canada, and there is some evidence that temperature and accumulated precipitation are significant predictors of O. ostertagi serum antibody concentrations [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations